Obstructive Sleep Apnea (OSA) - Rasjid HS, Mariani; Yogiarto, Mohammad (Medika Tadulako: Jurnal Ilmiah Kedokteran Fakultas Kedokteran dan Ilmu Kesehatan, 2015)
Obstructive sleep apnea (OSA) is a disease characterized by periodic upper airway collapse during sleep, which could result in either apnea, hypopnea or both. OSA is very often undetected but it is strongly associated with variety of medical complication, among others cardiovascular diseases. A good understanding can help physicians to diagnose, manage and prevent cardiovascular complication that caused by OSA.Â Keywords: Obstructive sleep apnea, cardiovascular